Milk scandal could have been avoided with Olympic ideals - Abd Razak, Dzulkifli (2008)
BARELY a month ago, the Beijing Olympics 2008 awed billions of people around the world with its organisation and performances despite several uncertainties. These include the many unprecedented challenges that the Olympics had to put up with, well before its glamorous opening ceremony on that auspicious 08.08.08. Some attempted to link them to the four elements that are popular among the Chinese—wind, earth, fire and water. They claimed that the freak snow storm that hit parts of that country and caused hundreds of thousands to be stranded from reaching their destinations was due to the wind element. The threat of fog and pollution then was another.